2001
DOI: 10.1001/jama.285.12.1581
|View full text |Cite
|
Sign up to set email alerts
|

Physical Abuse of Women Before, During, and After Pregnancy

Abstract: Since well-baby care use is similar for abused and nonabused mothers, pediatric practices may be important settings for screening women for violence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
90
4
8

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 295 publications
(121 citation statements)
references
References 23 publications
(16 reference statements)
17
90
4
8
Order By: Relevance
“…Women who had symptoms of anxiety also reported symptoms of PTSD-HIV. Our findings were consistent with research indicating a correlation between trauma, depression, and anxiety (Martin et al, 2001;Rosen et al, 2007;Tolman & Rosen, 2001).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Women who had symptoms of anxiety also reported symptoms of PTSD-HIV. Our findings were consistent with research indicating a correlation between trauma, depression, and anxiety (Martin et al, 2001;Rosen et al, 2007;Tolman & Rosen, 2001).…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with the general literature on HIVinfected women with a trauma history (Martin et al, 2001;Rosen et al, 2007;Tolman & Rosen, 2001), we found depression and anxiety as two of the most commonly reported psychological symptoms in our cohort. Nearly all of the women in our sample reported depressive symptoms during the pregnancy.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Estimates of rates of violent victimization in the year prior to birth, including during pregnancy, have ranged from 1% to 34% (Cokkinides & Coker, 1998; Huth-Bocks, Levendosky, & Bogat, 2002; Jasinski, 2004; Martin, Mackie, Kupper, Buescher, & Moracco, 2001; Reichenheim & Moraes, 2004; Sagrestano, Carroll, Rodriguez, & Nuwayhid, 2004). Variation in these rates is likely a result of different samples, measures, and criteria for determining whether violence has occurred (Jasinski, 2004).…”
Section: Levels Of Violence Among Expectant Parentsmentioning
confidence: 99%
“…Although qualitative studies have suggested that pregnancy may contribute to the onset and/or the increase of IPV (Edin, Dahlgren, Lalos, & Hogberg, 2010;Hussain & Khan, 2008;Jeanjot et al, 2008;Williams & Brackley, 2009), other studies have suggested that IPV during pregnancy is a continuation of earlier violence and is likely to continue following the baby's birth (Campbell, Oliver, & Bullock, 1993;Edin et al, 2010;Heding, 2000;Martin et al, 2001).…”
mentioning
confidence: 99%